FENOMENA MENURUNNYA MINAT MEMBACA BUKU CETAK DI KALANGAN MAHASISWA PGMI UIN STS JAMBI - Dini Dini wahyuni (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2026)
This study aims to analyze the factors influencing the decline in interest in reading printed books among students of the Islamic Elementary School Teacher Education Program (PGMI) at UIN Sultan Thaha Saifuddin Jambi. The study employs a qualitative approach with a field research design to gain an in-depth understanding of students’ experiences, behaviors, and perceptions regarding reading printed books. Data were collected through in-depth interviews, direct observation, and documentation of students selected using purposive sampling, supplemented by lecturers as additional informants. Data analysis was conducted through data reduction, data presentation, and drawing conclusions, with validity maintained through source and method triangulation. The results indicate that the decline in interest in reading printed books is primarily influenced by easy access to digital information, the perception that printed books are less attractive and time-consuming, limited encouragement from the academic environment, and insufficient library facilities and collections. This situation impacts students’ deep comprehension of materials, limits the use of academic references, and reduces active participation in learning activities. These findings highlight the need for learning strategies that promote effective use of printed books while utilizing digital technology proportionally, ensuring that students maintain adequate academic literacy skills and are prepared to become competent future educators.